Dinamika Penalaran Moral pada Pendidikan Militer Indonesia, Sebuah Studi Kualitatif - Indriyani Santoso; M Satria; Aneiza (HK Publishing, 2025)
The purpose of this study is to examine the dynamics of moral reasoning and deference to authority in people with military training. 21 respondents completed an open-ended questionnaire as part of an exploratory qualitative method. The data were analyzed using Interpretative Phenomenological Analysis (IPA) and triangulated to guarantee the validity of the results. Three primary themes emerged from the study's findings: (1) the conflict between personal morals and career sustainability, where some respondents chose to uphold moral integrity despite the risk to professional stability, while others were willing to sacrifice personal values for loyalty; (2) obedience as identity and loyalty, where obedience has been internalized as an expression of institutional loyalty and part of collective moral identity; and (3) the decision-making process and moral moral disengagement, where the mechanism of shifting responsibility to superiors emerged, but some also showed moral engagement through consideration of intention and context. These results emphasize how crucial ethics education is for security institutions to strike a balance between moral duty and authoritarian discipline. The study's findings suggest that moral courage-based ethics education should strike a balance between moral responsibility and authoritarian discipline.